Cellular automata in damage mechanics: creep rupture case - Chrzanowski, M.; Nowak, K. (Archives of Mechanics, 2007)
In the paper, the cellular automata (CA) method for the description of damage formation introduced in [1], is extended over creep circumstance by introducing grain boundaries. The material structure is modelled by Voronoi-like tessellation with distance measure corresponding to Moore neighbourhood. The size of Representative Volume Element (RVE) is determined by the number of grains, seed nodes of which are distributed by a homogeneous Poisson point process. The global number of cells to be damaged is subjected to the mass conservation law. Additionally, probabilistic rules, which cause the damage to develop in form of microcracks, microvoids, large voids or a combination of voids and cracks are used. Loading through imposed deformation of RVE is continued until damage cells form a continuous path spanning opposite sides of RVE. In terms of continuum damage mechanics, this situation corresponds to the damage parameter reaching the critical value in a given material point. The results obtained in this paper for polycrystalline material have been compared with a material of homogenous structure.